Microcomputer applications - Price, Wilson T. (Chicago : Dryden Press, 1989)
Part one of the book provides readers with the necessary background to work with computer, the remaining part are application software.
"Featuring: WordPerfect, Lotus 1-2-3, and Joe Spreadsheet (a 1-2-3 Workalike) dBASE III PLUS."
System requirements for computer data disk: IBM PC, XT, AT, PS/2, or the equivalent; MS-DOS; 1-2 disk drives of hard disk.
Includes index.
ii 15/01/2019
Loans
Keywords: Microcomputers